Evaluation of enzymatic Pectin extraction by a recombinant Polygalacturonase (pgi) from apples and pears pomace of argentinean production and characterization of the extracted pectin - Franchi, María Luisa (2014)
Argentina produces, annually, 1.8 million tons of pome fruit, distributed almost equally between apple and pear. These fruits, produced in the High Valley of Río Negro are already a registered brand in the world of fruit. Aspergillus kawachii produces an acidic polygalacturonase (PGase) called PGI that has attracted considerable interest because of its potential use in the food industry, particularly those involving fruit production in this region (such as pectin extraction). The enzyme was cloned and expressed in Saccharomyces cerevisiae. The objective of this work was to evaluate the use of PG1 in the enzymatic pectin extraction from apples and pears pomace. Characterization of the extracted pectin was also done. The performance of PGI extraction process was compared to the traditional chemical extraction process and to the enzymatic extraction with commercial enzymes. The esterification degree and the content of uronic acids from the pectin obtained were determined. In all cases, the extraction with PGI had higher yields than the chemical extraction process. Enzymatic extracted pectins exhibited an esterification degree> 50% so that they can be considered belonging to the group of high methoxylpectins. According to these results, PGI could be used to produce pectins from fruit pomaces converting these materials, currently considered wastes, into by-products of the fruit industry.